Design of a toolbox for kinematic analysis of jansen's linkage - YILDIRIM, ALPER (My University, 2022)
Utilizing industrial robots is an efficient method for addressing the labor crisis and advancing industrial technologies. As a result, industrial robots are becoming increasingly popular. Additionally, the widespread use of industrial robots will increase the interest in robot propulsion mechanisms. Legged robots should be primarily investigated because of their potential advantages. Among leg mechanisms, Jansen\"s linkage (JL) has gained popularity due to its organic walking motion, scalable design, and simple drive by rotary input. However, the highly nonlinear nature of JL makes its analysis challenging. The research provides a user-friendly toolbox design that visualizes the toe trajectory and simultaneously calculates the step height by performing a kinematic analysis of the JL using the user-supplied link lengths. In this way, the study contributes significantly to the design phase of legged robots and reduces the amount of time required.
Keywords: Bilgisayar Bilimleri; Yapay Zeka, Bilgisayarda Öğrenme ve Örüntü Tanıma; Mühendislik ve Teknoloji; Computer Sciences; Artificial Intelligence, Computer Learning and Pattern Recognition; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; Bilgisayarla Görme ve Örüntü Tanıma; Bilgisayar Bilimi Uygulamaları; Yapay Zeka; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Fizik Bilimleri; Computer Vision and Pattern Recognition; Computer Science Applications; Artificial Intelligence; Computer Science (miscellaneous); General Computer Science; Physical Sciences